PENGARUH FASILITAS DAN AKSESIBILITAS TERHADAP KEPUASAN WISATAWAN MILLENIAL DI PARALAYANG WAYU, SULAWESI TENGAH - Amalia, Putri Amibiyah Ihlasul; Wijaya, NMS.; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p11, 2022)
Accessibility and facility are regarded as important component for tourist satisfaction and development of tourist attraction. Central Sulawesi is currently developing regional tourism potential with optimize tourism in three priority tourist destinations, one of them is paralayang wayu. The purpose of this research is to know the tourist characteristic and analyse the effect of facilility and accessibility on tourist satisfaction in paralayang wayu. Data was collected through questionnaires using purposive random sampling. The respondent were 110 tourist. Beside surveys, data was obtained through observation, interview and literature studies. It’s analyzed using multiple linear regression, hypothesis testing and coefficient of determination and classical assumption test. The results of the study partially show that the facilities have a significant effect on millennial tourist satisfaction with a t count of 6.331 and a significant value of 0.000. Accessibility variables have a significant effect on millennial tourist satisfaction with a t count of 3.603, a significance of 0.003. Simultaneously facilities and accessibility have a significant effect on millennial tourist satisfaction with t count of 55,191 and a significant value of 0.000. Based on data analysis, the influence of facilities and accessibility on millennial tourist satisfaction is 50.8%, while 49.2% is explained by other variables not examined.